Sphingolipid Metabolism Is Dysregulated at Transcriptomic and Metabolic Levels in the Spinal Cord of an Animal Model of Amyotrophic Lateral Sclerosis - Henriques, Alexandre; Croixmarie, Vincent; Bouscary, Alexandra; Mosbach, Althéa; Keime, Céline; Boursier-Neyret, Claire; Walter, Bernard; Spedding, Michael; Loeffler, Jean-Philippe (Frontiers in Molecular Neuroscience, 2018)
Lipid metabolism is drastically dysregulated in amyotrophic lateral sclerosis and impacts prognosis of patients. Animal models recapitulate alterations in the energy metabolism, including hypermetabolism and severe loss of adipose tissue. To gain insight into the molecular mechanisms underlying disease progression in amyotrophic lateral sclerosis, we have performed RNA-sequencing and lipidomic profiling in spinal cord of symptomatic SOD1G86R mice. Spinal transcriptome of SOD1G86R mice was characterized by differential expression of genes related to immune system, extracellular exosome and lysosome. Hypothesis-driven identification of metabolites showed that lipids, including sphingomyelin(d18:0/26:1), ceramide(d18:1/22:0) and phosphatidylcholine(o-22:1/20:4) showed profound altered levels. A correlation between disease severity and gene expression or metabolite levels was found for sphingosine, ceramide(d18:1/26:0), Sgpp2, Sphk1 and Ugt8a. Joint-analysis revealed a significant enrichment of glycosphingolipid metabolism in SOD1G86R mice, due to the down-regulation of ceramide, glucosylceramide and lactosylceramide and the overexpression of genes involved in their recycling in the lysosome. A drug-gene interaction database was interrogated to identify potential drugs able to modulate the dysregulated genes from the signalling pathway. Our results suggest that complex lipids are pivotally changed during the first phase of motor symptoms in an animal model of amyotrophic lateral sclerosis.